Peningkatan Pengetahuan Dan Kunjungan Pasien Pada Unit Pelayanan Kesehatan Tradisional Terintegrasi Melalui Media Tiktok - Suryaningrum, Wasiska; Haris, Mustofa; Fitriah, Fitriah; Zainiyah, Zakkiyatus; Anggraeni, Novi; Jannah, Rohilatul (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
More than 50% of respondents in outpatient clinics at five Community Health Centers (Puskesmas) in the working area of Sampang Regency were not aware of the availability of integrated traditional health services. This study aims to increase public knowledge of integrated traditional health services and to increase the number of visits to these units. The research method used was Research and Development. Subjects were selected using simple random sampling with a total sample of 175 participants. The analysis in this study was designed using the ADDIE model. The results showed an increase in public knowledge and an increase in the number of visits to the service units, reaching an average of 3–29 patients per month at each Puskesmas. To increase viewership and interest in TikTok content, it is recommended that Puskesmas develop more engaging animated video content, rather than relying solely on videos containing e-leaflets.